2019
DOI: 10.1002/ldr.3281
|View full text |Cite
|
Sign up to set email alerts
|

Selection of suitable species as a key factor for vegetation restoration of degraded areas in an open‐pit manganese‐ore mine in Southern China using multivariate‐analysis methods

Abstract: Open‐pit mining results in large amounts of degraded lands that require ecological recovery. Adequate‐species selection for ecological recovery is of great importance. In this study, field investigations along the disturbance gradients (marginal area, restoration area, and control area) in a manganese ore deposit of Guangxi in Southern China were carried out. We screened the adequate species from two aspects. In the marginal area, the result of corrected Akaike information criterion revealed that Mn was the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 59 publications
(69 reference statements)
0
9
0
1
Order By: Relevance
“…High (GRNDVI level: 1.75-2.00) and remarkable vegetation growth (GRNDVI level: 2.00-4.00) had the high proportion in 2016 and 2018, accounting for 37.96% (12.103 km 2 ), and 29.96% (9.552 km 2 ), respectively. Some factors, such as climate, soil, and topography, are critical to the changes for the inter-annual vegetation growth [42][43][44]. The area of bare land increased from 0.414 km 2 in 2011 to 6.236 km 2 in 2018 and the area of bare land had been basically expanding.…”
Section: Inter-annual Vegetation Growth Results and Cross-validationmentioning
confidence: 99%
“…High (GRNDVI level: 1.75-2.00) and remarkable vegetation growth (GRNDVI level: 2.00-4.00) had the high proportion in 2016 and 2018, accounting for 37.96% (12.103 km 2 ), and 29.96% (9.552 km 2 ), respectively. Some factors, such as climate, soil, and topography, are critical to the changes for the inter-annual vegetation growth [42][43][44]. The area of bare land increased from 0.414 km 2 in 2011 to 6.236 km 2 in 2018 and the area of bare land had been basically expanding.…”
Section: Inter-annual Vegetation Growth Results and Cross-validationmentioning
confidence: 99%
“…Many tropical landslides are quickly colonized by Gleicheniaceae [118]. Among the seven high-disturbance indicators, previous studies found that Dicranopteris pedata and Blechnum orientale dominate the early successional stage on landslide trails [119]; Odontosoria chinensis frequently colonizes disturbed places [120]; Lygodium microphyllum has the ability to invade hurricane-disturbed areas [121]; Cyclosorus parasiticus adapts to disturbed habitats [122]; Christella dentata is common along roadsides but can also dominate in undisturbed, lightly disturbed, and moderately disturbed forests [123], which makes it a poor disturbance indicator; Pteris semipinnata is a dominant understory species in the economic needle-leaf forest of Pinus massoniana [124]. Our results are thus in accordance with the previous observations and point to a certain generality of the results obtained by us.…”
Section: Indicator Fern Species For Different Disturbance Levelsmentioning
confidence: 99%
“…Together with the improvement of soil properties, the selection of suitable plant species is fundamental to guarantee the success of restoration programs in abiotically stressful areas [22,23]. Plant selection for plantation in mine tailings has evolved from the use of model species towards the use of local species adapted to barren substrates that are able to tolerate (but not accumulate) metal(loids) [11,19,24,25].…”
Section: Introductionmentioning
confidence: 99%